Composite‐modified anode by MnO2/polypyrrole in marine benthic microbial fuel cells and its electrochemical performance. (7th November 2016) - Chen, Wei; Liu, Zhaohui; Su, Ge; Fu, Yubin; Zai, Xuerong; Zhou, Changyang; Wang, Jian
Summary: Low power limits the application of microbial fuel cells (MFCs). Our research mainly focuses on the modification of the electrode and looking for new anode material for high‐power marine benthic microbial fuel cells(BMFCs). A MnO2 /PPy composite‐modified anode was fabricated by in situ chemical polymerization. Surface topography and properties were characterized by scanning electron microscopy and infrared spectroscopy, respectively, indicating that the MnO2 /PPy composite is of a 'mosaic‐like' microstructure. The electrochemical performance and wettability of different kinds of anode were investigated respectively. Cyclic voltammetry and linear sweep voltammetry tests show that MnO2 /PPy composite‐modified electrode has a typical capacitance feature; its capacitance is 3.1 times higher than that of unmodified electrode. Contact angle of the composite‐modified anode reduces to 46 ± 0.5°, and its kinetic activity increased for more than 1.1 times. The maximum output power density of MnO2 /PPy composite‐modified cell reached 562.7 ± 10 mW m −2, which is 2.1‐fold of the unmodified one. Finally, the composite‐modified anode provides an alternative potential choice for high‐performance cell, and the possible influence mechanism of composite materials on the BMFCs was also analyzed. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A MnO2 /PPy composite‐modified anode was fabricated by in situ chemical polymerization. The MnO2 /PPy composite is of a "mosaic‐like" structure, and the BMFCs modified by it show much better performance than unmodified ones. The composite increases the pseudocapacitance of anode and electronic transmission channels; meanwhile, the manganese ions accelerate the electron transfer rate as an electron transfer intermediary.